An Analysis of Computational Performance of Different Quantum Circuits on Different IBMQ Backends: Case Study - Yetis, Hasan; Karakose, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2023)
Quantum computers are difficult to reach by researchers because of the difficulty in manufacturing technologies and the need to provide ideal working conditions. As a solution, IBM Quantum (IBMQ) systems developed by IBM are accessed via the cloud. Although there are high qubit quantum backends currently offered for a fee, 5 and 7 qubit backends are publicly free. In this study, publicly free quantum backends in the IBM quantum experience environment are discussed. The study includes a comparative explanation of the factors affecting the performance of quantum computers. Quantum circuits were created in the IBM Composer environment and then run on the appropriate backend. Quantum circuits of 4mod5, which finds whether a 4-bit number is divisible by 5, 1-bitadder that performs 1-bit addition with the carry bit, and gray code, which finds the gray code equivalent of the binary number, were created. The created circuits were run on 8 different IBMQ backends and the results were analyzed. As a result of the analysis, it has been shown that while the simplicity of the gates used increases the performance rates, there may be different backends that operate each quantum circuit more accurately. It is hoped that the study will be a guide for researchers working on applied quantum computing. © 2023 IEEE.
4th International Conference on Data Analytics for Business and Industry, ICDABI 2023 -- 25 October 2023 through 27 October 2023 -- Virtual, Online -- 201891
Keywords: applied quantum computing; IBM quantum experience; quantum circuits; quantum computers